MODAL POLITIK H. SUKARMIS PADA PEMILIHAN UMUM LEGISLATIF TAHUN 2019 DAPIL VIII RIAU - Fitri Ramadhani; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Political capital is a force that legislative candidates must have when they want to compete in a democratic party. Because political capital in the form of economic capital, social capital, cultural capital, and symbolic capital is very effective in winning political contestation. The method used in writing this research is a qualitative approach. Meanwhile, the keyinformants used were 7 people. Data collection methods are by using interviews and documentation. The findings prove that the synergy of various political capitals is very significant in determining one's victory in political contestation and at the same time giving high-cost political burdens to legislative candidates. The case of H. Sukarmis' victory in the political contestation of the legislative elections in the Electoral District VIII in 2019 has proven the importance of politics. H. Sukarmis had the advantage of social and cultural capital that his political opponents had never imagined, so he was able to displace other powerful figures who rely more on symbolic and economic capital alone. This proves that social capital economic capital, cultural capital, and symbolic capital, must be combined to win political contestation, especially general elections. Because if one capital is not used optimally, it will tend to have an impact on other capital. For example, a lack of social capital will increase campaign costs.  Keywords: Economic Capital, Social Capital, Cultural Capital, Symbolic Capital.